THE EFFECT OF TEAM GAMES TOURNAMENT LEARNING MODEL ON COOPERATION ABILITY, MOTIVATION AND COGNITIVE LEARNING OUTCOMES OF GRADE XI IPA STUDENTS - Turnip, Ayu Monita; Sipahutar, Herbert (Universitas Negeri Medan, 2025)
This study was aimed to determine the effect of the TGT learning model on students’ cooperation skills, motivation and cognitive learning outcomes on the Blood Circulatory System in class XI SMA Negeri 13 Medan academic year of 2023/2024. This type of research is a quasi-experimental with Pre- and Post-test Control Group Design. This study used two classes, namely class XI 6 as the experimental class taught with the TGT learning model and class XI 5 as the control class with Direct Instruction learning model. The results showed that the average score of students' cooperation skills in the experimental class 86%, was higher than the control class 64% (t test, p < 0.05). The average score of student motivation in the experimental class (80.13) was significantly higher than the control class (67.67) (t test, p < 0.05). While the average post-test score of student learning outcomes in the experimental class (80.00) was significantly higher than the control class (72.22). Based on these results, it is concluded that the TGT learning model has an significant effect to improving students' cooperation skills, motivation and cognitive learning outcomes in the Blood Circulatory System material in class XI SMA Negeri 13 Medan TP 2023/2024.